Visualization of volumetric datasets - Dartu, Catalin (Ruprecht-Karls-Univ., 2001)
Visualisation, volumetric datasets, volume rendering, image processing
Contract BMBF 03JA7 HE1 6. - Differences between the printed and electronic version of the document are possible. - nBibliography p. 70 - 71
Also available as printed version
Keywords: Forschungsbericht